A mirror that reflects your pupils every day (Journal of Parents and Teachers, 2016)
In the following article, it talks about the teacher’s training experience through the four years of the Primary Education degree. All the experiences and reflections about everything that is learnt at university and the schools are written, at the same time the feedback that is given and the information by the forum, teacher’s school, university’s supervisor and the auto reflection of one student who is doing the teacher’s training.
Keywords: Experience; education; teacher’s training; school; learning; reflection; vocation; participation; pragmatist; profession; teaching.